Structural Productivity Convergrence of Rcep - Dyg Affizzah, A. M.; Awgku Alizra, A. A.; Ting, Mee Sing (HRMARS, 2020)
This study aimed is to test the convergence on value added share of four major sectors namely manufacturing, services, agriculture and construction within a group of selected Regional Comprehensive Economic Partnership (RCEP) referring to Malaysia, Brunei Darussalam, Singapore, Thailand, Indonesia, Philippines, Japan, South Korea, China, India, Australia and New Zealand. From the finding it shows that there is no panel structural convergence found in all four sectors for all the countries. However, it does not indicate that there is no possibility of convergence because a country might cluster with another country. Among the four major sectors, agricultural sector shows the most diverse formation of convergence indicating vast gap in its agricultural sector development among the RCEP countries. Yet manufacturing sectors shows more similarities and common characters shared by countries in the study. In other words, RCEP countries are more similar in its development in term of its manufacturing performance. Structural convergence is indeed essential to strengthen the integration of economics in order to achieve the objective of RCEP Based on the results, a country ought to build regional linkages with another country as well as examine their own similarities with other regions. When the countries happen to share similar structural economy, any form of external shocks will result in symmetric but depending on the areas.